Gut Microbiome Alterations and Hepatic Metabolic Flexibility in the Gansu Zokor, Eospalax cansus: Adaptation to Hypoxic Niches - Lin, Jinyan; Yang, Qi; Guo, Juanjuan; Li, Meng; Hao, Zhiqiang; He, Jianping; Li, Jingang (Frontiers in Cardiovascular Medicine, 2022)
The Gansu zokor (Eospalax cansus), a typical subterranean rodent endemic to the Chinese Loess Plateau, spends almost the whole life in its self-constructed underground burrows and has strong adaptability to ambient hypoxia. Energy adaptation is the key to supporting hypoxia tolerance, and recent studies have shown that the intestinal microbiota has evident effect on energy metabolism. However, how the gut microbiome of Gansu zokor will change in response to hypoxia and the metabolic role played by microbiome have not been reported. Thus, we exposed Gansu zokors to severe hypoxia of 6.5% O2 (6 or 44 hours) or moderate hypoxia of 10.5% O2 (44 hours or 4 weeks) and then analyzed 16S rRNA sequencing, metagenomic sequencing, metagenomic binning, liver carbohydrate metabolites and related molecular levels. Our results showed that hypoxia altered the microbiota composition of Gansu zokor, and the relative contribution of Ileibacterium to carbohydrate metabolism became increased under hypoxia, such as glycolysis and fructose metabolism. Furthermore, Gansu zokor liver enhanced carbohydrate metabolism under the short-term (6 or 44 hours) hypoxia but it suppressed under the long-term (4 weeks) hypoxia. Interestingly, under all hypoxia conditions, Gansu zokor liver exhibited enhanced fructose-driven metabolism through increased expression of the GLUT5 fructose transporter, ketohexokinase (KHK), aldolase B (ALDOB) and aldolase C (ALDOC), as well as increased KHK enzymatic activity and fructose utilization. Overall, our results suggest that the altered gut microbiota mediates carbohydrate metabolic pattern under hypoxia, possibly contributing to the hepatic metabolic flexibility in Gansu zokor, which leading to better adaptation to hypoxic environments.